Integrated and Portable Magnetometer Based on Nitrogen‐Vacancy Ensembles in Diamond. Issue 4 (10th February 2021) - Stürner, Felix M.; Brenneis, Andreas; Buck, Thomas; Kassel, Julian; Rölver, Robert; Fuchs, Tino; Savitsky, Anton; Suter, Dieter; Grimmel, Jens; Hengesbach, Stefan; Förtsch, Michael; Nakamura, Kazuo; et al.
Abstract: Magnetic field sensors that exploit quantum effects have shown that they can outperform classical sensors in terms of sensitivity enabling a range of novel applications in future, such as a brain machine interface. Negatively charged nitrogen‐vacancy (NV) centers in diamond have emerged as a promising high sensitivity platform for measuring magnetic fields at room temperature. Transferring this technology from laboratory setups into products and applications, the total size of the sensor, the overall power consumption, and the costs need to be reduced and optimized. Here, a fiber‐based NV magnetometer featuring a complete integration of all functional components is demonstrated without using any bulky laboratory equipment. This integrated prototype allows portable measurement of magnetic fields with a sensitivity of 344 pT Hz −1/2 . Abstract : Negatively charged nitrogen‐vacancy centers in diamond are a promising candidate for high sensitive magnetometers enabling wide range of applications. Transferring this technology into products, this sensor needs to be miniaturized and integrated such that it can be portably used without the requirement of bulky laboratory equipment. A portable prototype of a fiber‐integrated magnetometer with sub‐nanotesla sensitivity is demonstrated.